Rural exposure during medical education and student preference for future practice location - a case of Botswana - Tonya Arscott-Mills; Poloko Kebaabetswe; Gothusang Tawana; Deogratias O. Mbuka; Orabile Makgabana-Dintwa; Kagiso Sebina; Masego Kebaetse; Lucky Mokgatlhe; Oathokwa Nkomazana (AOSIS, 2016)
Background: Botswana's medical school graduated its first class in 2014. Given the importance of attracting doctors to rural areas the school incorporated rural exposure throughout its curriculum. Aim: This study explored the impact of rural training on students' attitudes towards rural practice. Setting: The University of Botswana family medicine rural training sites, Maun and Mahalapye. Methods: The study used a mixed-methods design. After rural family medicine rotations, third- and fifth-year students were invited to complete a questionnaire and semi-structured interview. Data were analysed using descriptive statistics and thematic analysis. Results: The thirty-six participants' age averaged 23 years and 48.6% were male. Thirtythree desired urban practice in a public institution or university. Rural training did not influence preferred future practice location. Most desired specialty training outside Botswana but planned to practice in Botswana. Professional stagnation, isolation, poorly functioning health facilities, dysfunctional referral systems, and perceived lack of learning opportunities were barriers to rural practice. Lack of recreation and poor infrastructure were personal barriers. Many appreciated the diversity of practice and supportive staff seen in rural practice. Several considered monetary compensation as an enticement for rural practice. Only those with a rural background perceived proximity to family as an incentive to rural practice. Conclusion: The majority of those interviewed plan to practice in urban Botswana, however, they did identify factors that, if addressed, may increase rural practice in the future. Establishing systems to facilitate professional development, strengthening specialists support, and deploying doctors near their home towns are strategies that may improve retention of doctors in rural areas. Keyords: rural health, student perceptions